2009
DOI: 10.1055/s-0029-1211139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylcholine on the Release of Thyrotropin-Releasing Hormone from the Rat Retina in vitro

Abstract: Effects of acetylcholine on the release of thyrotropin-releasing hormone (TRH) from the rat retina were studied in vitro. The retina was incubated in medium 199 (pH 7.4) with 1.0 mg/ml of bacitracin and 100 micrograms/ml of ascorbic acid (medium) for 20 min. The amount of TRH release into the medium was measured by radioimmunoassay. The TRH release from the rat retina was enhanced significantly in a dose-related manner with the addition of acetylcholine and inhibited with addition of atropine. The stimulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is known that TRH concentrations in the retina are influenced by light (Shaeffer et al, 1977;Marino et al, 1980) and that SS acts at multiple levels within the retinal circurity to produce the observed changes in ganglion cell output (Sagar and Marshall, 1989) and the excitation of ganglion cells to light is modified by SS (Zalutsky and Miller, 1990). TRH from the rat retina is stimulated by acetylcholine and inhibited by dopamine and serotonin (Mitsuma et al, 1992a;Mitsuma et al, 1992b;Mitsuma et al, 1996). These data indicate that both TRH and SS in the retina may share some retinal function.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It is known that TRH concentrations in the retina are influenced by light (Shaeffer et al, 1977;Marino et al, 1980) and that SS acts at multiple levels within the retinal circurity to produce the observed changes in ganglion cell output (Sagar and Marshall, 1989) and the excitation of ganglion cells to light is modified by SS (Zalutsky and Miller, 1990). TRH from the rat retina is stimulated by acetylcholine and inhibited by dopamine and serotonin (Mitsuma et al, 1992a;Mitsuma et al, 1992b;Mitsuma et al, 1996). These data indicate that both TRH and SS in the retina may share some retinal function.…”
Section: Resultsmentioning
confidence: 92%
“…TRH and SS are known to be a transmitter in the retina (Bolz and Thier, 1985;Ehinger, 1985;Zalutsky and Miller, 1990;Watt and Florack, 1994). We previously reported that TRH release from the rat retina was influenced by amines (Mitsuma et al, 1992a;Mitsuma et al, 1992b;Mitsuma et al, 1996). Furusawa et al reported that the release of TRH or SS from the rat stomach was inhibited by each other (Furusawa et al, 1992).…”
Section: Introductionmentioning
confidence: 99%